Small bowel perforation secondary to foreign body ingestion mimicking appendicitis: a case report - Medhi, Bijit B.; Gupta, P. D.; Tauheed, Fahad; Chauhan, Vikram Singh (International Surgery Journal, 2021)
Admittance in the emergency room with complaints of acute abdominal pain is a common scenario. Patients who see the doctor due to foreign object ingestion present transitory symptomatology. In most cases, foreign object ingestion in adults is accidental, although it may be linked to physiological, anatomical, mechanical, social and psychiatric factors. The frequency of voluntarily ingested objects is higher among children and teenagers than in any other age group. Few people go to the doctor because of persistent clinical manifestations or secondary manifestations of previous complications. In most cases, the foreign body is found incidental to another medical procedure. Here we report a case of small bowel perforation due to ingestion of a sharp foreign body in a 2 years old child. We further elaborate that how, in paediatric age group these conditions are frequently misdiagnosed and usually present late to us. Hence, the increasing need and importance of a thorough pre-op workup, especially in the pediatric age group.